2022
DOI: 10.1371/journal.pone.0266266
|View full text |Cite
|
Sign up to set email alerts
|

Wavelengths and irradiances modulate the circadian rhythm of Neurospora crassa

Abstract: The circadian rhythm affects the biological evolution and operating mechanisms of organisms. The impact of light on the circadian rhythm is a significant concern for both biology and human well-being. However, the relation between different wavelengths, irradiances, and circadian rhythm is unknown. In this study, we compared the effects of four different monochromatic light-emitting diode (LED) light and two different irradiances on the circadian rhythm of a wild-type Neurospora crassa. The results demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Studies on children [ 29 ] and adolescents [ 30 ] have shown that exposure to a high CCT light environment in the evening could affect sleep quality and reduce sleepiness, compared with a low CCT light environment. Previous studies have further indicated that high CCT light could affect circadian rhythm [ [31] , [32] , [33] ] and influence sleep quality [ 34 ]. Further, in the current study, of the positive effect of low CCT light on sleep quality in adolescents was significant and prominent from the first day of the light intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on children [ 29 ] and adolescents [ 30 ] have shown that exposure to a high CCT light environment in the evening could affect sleep quality and reduce sleepiness, compared with a low CCT light environment. Previous studies have further indicated that high CCT light could affect circadian rhythm [ [31] , [32] , [33] ] and influence sleep quality [ 34 ]. Further, in the current study, of the positive effect of low CCT light on sleep quality in adolescents was significant and prominent from the first day of the light intervention.…”
Section: Discussionmentioning
confidence: 99%